Surabaya Millenial Phenomenological Study In Search Of Healthy Lifestyle Information Using Social Media: Social Media, Millenials, Athletes, Non Athletes, Healthy Lifestyle - Dewi Gunawan, Christina Maria Claudia Kusuma; Dewi Gunawan, Christina Maria Claudia Kusuma; S.I.P., M.Si., Gilang Gusti Aji (The Commercium, 2022)
A healthful way of life is a concern for anybody who desires to run it. Ease of getting access to healthful way of life statistics may be executed via social media by milenials. The reason of this observe turned into to decide the phenomenon of the usage of social media as a device to locate statistics on healthful lifestyles. The examine used a qualitative technique with statistics series strategies have been in-intensity interviews. Nine samples were selected using snowball sampling with three sample groups consisting of a group of athletes, non-athletes who have been implementing a healthy lifestyle for a long time, and non-athletes who have just started implementing a healthy lifestyle. The results showed that social media became a tool for all samples of each group in finding information on healthy lifestyles related to food, drink, and exercise. The end of this examine is that the group of athletes who are pro-healthy lifestyles, groups of non-athletes who have been running a healthy lifestyle for a long time, and groups of non-athletes or people who are new to a healthy life use social media to find information on healthy lifestyles. Instagram and YouTube are social media that are most often used to find food, drinks, and sports to support a healthy lifestyle.